IMPROVING NUMERACY SKILLS OF ELEMENTARY SCHOOL STUDENTS THROUGH PROBLEM-BASED LEARNING: AN IMPLEMENTATION OF LESSON STUDY - Mu'jizatin Fadiana; Yulaikah Yulaikah; Zenny Taufikurrizal (Universitas Islam Malang, 2022)
One of the basic literacy that can be applied in primary school education is numeracy literacy. The purpose of this study was to describe the increase in numeracy literacy skills of elementary school students at SD Bina Anak Sholeh (Islamic Fullday School) in Tuban through problem-based learning. This research was conducted in Class V-B for the academic year 2021/2020, which consisted of 27 students. Problem-based learning is carried out with a lesson study approach which includes three stages, namely plan (planning), do (implementation), and see (observation and reflection) for each cycle. The results showed that the problem-based learning model could be applied to improve the numeracy literacy skills of elementary school students. The ability of teachers to develop problem-based learning plans, present problems in the form of literacy, plan learning strategies and develop numeracy literacy assessment instruments. The numeracy literacy ability of elementary school students has increased.